A Preliminary Study on the Solvent Extraction of Molybdenum and Rhenium from an Industrial Pregnant Leach Solution Using Alamine336 as the Extractant and the Ionic Liquid 1-Octyl-3-Methylimidazolium Bis(trifluoromethylsufonyl)imide as the Diluent - Quijada-Maldonado, E; Araya-Orrego, A; Urzua-Ahumada, J; Saleh-Hayat, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
A study on the selective solvent extraction (SX) of molybdenum (Mo) and rhenium (Re) from two industrial pregnant leach solutions (PLSs) was carried out using Alamine 336 as the extractant and the ionic liquid (IL) 1-octyl-3-methyl Imidazolium bis (trifluoromethylsulfonyl) imide [Omim][Tf2N] as the diluent. One industrial PLS was rich in Mo (VI) (PLS-Mo) and the second one rich in Re (VII) (PLS-Re). Experiments were carried out in open vials in which the concentration of Alamine336 in the diluent, the aqueous-to-organic ratio (A/O), and the stripping with ammonium carbonate (NH42CO3) were carried out systematically. Results indicate that decreasing the aqueous-to-organic (A/O) ratio led to an enhancement in the extraction performances of both Mo (VI) and Re (VII), reaching recoveries of 95%-98% at an A/O ratio of 1:1. However, differences between PLSs became evident at higher ratios, as Re extraction declined more sharply than Mo. Third-phase formation was observed only in the Mo-containing PLS. The PLS-Re system did not exhibit the formation of a third phase due to a lower concentration of metal (1 g/L Mo). The use of ammonium carbonate for stripping led to enhanced recoveries, achieving 84.4% for Re and 46.8% for Mo. A total of 50 extraction-stripping cycles were carried out in this work. These demonstrated nearly total initial extraction, but performance decreased over the cycles because of insufficient stripping and solvent loading. Overall, [Omim][Tf2N] proved to be an effective and environmentally friendly alternative to conventional diluents for Mo and Re separation and recovery from industrial leach solutions.